The influence of relative humidity on the carrier particle surface characteristics used in dry powder inhalation formulation - M. Boshhiha, Antesar; A. Urbanetz, Nora (Libyan Journal of Science &Technology, 2022)
Purpose: Investigation of the effect of carrier storage at elevated relative humidities on the carrier surface fines. The resulted effects of this storage conditions on the carrier surface characteristics when mixed with micronized salbutamol sulphate and the subsequent in vitro deposition were investigated. Methods: Lactose (InhaLac120) and mannitol (Pearlitol160) carrier particles (112 µm – 140 µm) were subjected to different relative humidities for 6 weeks period of time in order to get a smoother surface. In vitro deposition carried out for those modified carriers after mixing with salbutamol sulphate using a Next Generation Impactor (NGI). The modified carriers were characterized by scanning electron microscope, Brunauer Emmet and Teller specific surface area determination, differential scanning calorimetry, X-ray powder diffraction and water vapour sorption in comparison with the treated carrier without added fines. Results: The modified lactose and mannitol carriers stored at different relative humidities starting from 35% RH-75% RH show no change in fine particle fraction (FPFs). Subsequently, the carrier storage at 95% RH shows a significant decrease in the in vitro drug release. This probably by increasing drug-carrier adhesion and show a difficult detachment of the drug particles from the carrier surface smoothed at 95% RH. Conclusions: Storage of lactose and mannitol carriers at different relative humidities up to 75% result in un-significant change in drug fine particle fraction using the NGI. Additionally, storage of those carriers at high relative humidity up to 95% RH found to decrease significantly the dispersion of the drug and subsequently the FPF in the in vitro deposition test.